La magia del lenguaje de los niños - Álvarez Angulo, Teodoro (Didáctica. Lengua y Literatura, 2002)
The aim of this article is to present a study about the developing of oral language in a child, from two years and four months up to seven. This study is focussed on the phonetic-phonological, lexical-semantic, morphosyntactic, creativity, expression and cultural components of the language. Furthermore, speech samples containing some phenomena present in the development of this child are showen.